Susceptibility of Aedes aegypti (L) to the insect growth regulators diflubenzuron and methoprene in Uberlândia, State of Minas Gerais Susceptibilidade de Aedes aegypti (L) aos reguladores de crescimento de insetos diflubenzuron e methoprene em Uberlândia, Estado de Minas Gerais - Juliana Junqueira da Silva; Júlio Mendes (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Aedes aegypti (L) (Diptera: Culicidae) was reared in several concentrations of diflubenzuron and methoprene under laboratory conditions in Uberlândia, State of Minas Gerais, southeastern Brazil. Characteristics such as LC50 and LC95, the susceptibility of immature stages of different ages to these insect growth regulators and their residual effects were studied. The LC50 and LC95 of diflubenzuron and methoprene were 5.19 and 12.24 ppb; 19.95 and 72.08 ppb, respectively. While diflubenzuron caused great mortality in all larval instars, methoprene was more effective when the mosquito was exposed from the start of the fourth larval instar onwards. Commercial concentrations of these two insect growth regulators close to LC95 presented greater residual activity than did their respective technical formulations. The parameters were compared with those obtained elsewhere. The characteristics investigated here indicate that these insect growth regulators are effective alternatives for controlling the dengue vector in the Uberlândia region. Aedes aegypti (L) (Diptera: Culicidae) foi criado em várias concentrações de diflubenzuron e methoprene sob condições de laboratório em Uberlândia, Minas Gerais, sudeste do Brasil. Foram estudados aspectos tais como, CL50 e CL95, suscetibilidade de estágios imaturos de diferentes idades a estes insect growth regulators e seu efeito residual. As CL50 e CL95 de diflubenzuron e methoprene foram: 5,19 e 12,24ppb; 19,95 e 72,08ppb, respectivamente. Enquanto diflubenzuron causou grande mortalidade em todos os estádios larvais, methoprene causou maior mortalidade quando o mosquito foi exposto a partir do início do quarto estádio larval. As concentrações comerciais dos dois insect growth regulators próximas às CL95 mostraram maior atividade residual que suas respectivas formulações técnicas. Os parâmetros são comparados com aqueles obtidos em outros locais. Os aspectos aqui investigados indicam estes insect growth regulators como alternativas efetivas para o controle do vetor da dengue na ...